THE NEW ERA OF FINANCIAL INNOVATION: THE DETERMINANTS OF BITCOIN’S PRICE - Sukmawati Sukamulja; Cornelia Olivia Sikora (Faculty of Economics and Business, Universitas Gadjah Mada, 2018)
Financial innovation has entered a new era in which a digitalized system and cryptocurrency have been created. This paper examines the factors that influence the price movement of bitcoin. This is not a legal currency in Indonesia; the Indonesian government has not made any regulations legalizing bitcoin’s use, but it has also not issued any new laws to prohibit the trade in bitcoins and other digital currencies. The demand for, and price growth of, bitcoin are interesting matters to study, especially for Indonesians who still have questions about the progress of Bitcoin transactions and the factors that influent them. In Indonesia itself, without any protection from the government, the bitcoin price on December 14, 2017 had already reached more than IDR224.5 million, compare to IDR60 million in October 2017. Bitcoin is the first peer-to-peer currency, and was introduced by Satoshi Nakamoto in 2008. Since its inception, bitcoin has served more than 17 million users, including Indonesians. Bitcoin behaves in a different manner, compared to traditional currencies and the one that affects bitcoin’s price is its attractiveness for investors. The Vector Error Correction Model (VECM) is applied to analyze the short-term and long-term influences. VECM is used in this research because the data is stationary in the first difference and has a cointegration relationship. To make the interpretation clearer, the impulse response function and variance decomposition also are included in this research. The result indicates that the macroeconomic indicator, represented by the Dow Jones Industrial Average (DJIA), the demand for bitcoins and the gold price influence bitcoin’s price fluctuations in the short-run and long-run. Bitcoin’s supply does not influence its price fluctuation in the long-run but does influence it in the short-run. The implication of this research is bitcoin could compete as an alternative investment compared to the capital markets and gold.